2017
DOI: 10.1590/1678-457x.37516
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin characteristics of wines in Vitis germplasms cultivated in southern China

Abstract: The anthocyanin profiles and COELAB color values of nine wines in Vitis germplasms from southern China were compared. The results showed that the anthocyanin composition of wines from one hybrid between V. vinifera and V. labrusca ('Moldova'), two V. labrusca varieties ('Conquistador' and 'Saint-Croix'), one V. quinquangularis variety ('Yeniang No.2'), one hybrid between V. quinquangularis and V. vinifera ('NW196'), one V. davidii variety ('Xiangniang No.1') and one V. rotundifolia variety ('Noble') were domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Thus, anthocyanin composition of V. vinifera grapes is widely different than these aforementioned Vitis species, in which non-acylated derivatives represent between 57 to 75 % of total anthocyanins compared to acetyl, coumaroyl and caffeoyl derivatives (Núñez, Monagas, Gomez-Cordovés, & Bartolomé, 2004;González-Neves et al, 2007; Castillo-Muñoz, Fernández-González, Gómez-Alonso, García-Romero, & Hermosín-Gutiérrez, 2009;Gutiérrez-Gamboa et al, 2017). Colorimetric analysis showed that the wines from V. quinquangularis specie presented the most saturated red color compared to other Vitis germplasms cultivated in South of China, such as Moldova (V. vinifera × V. labrusca), Conquistador and Saint-Croix (V. labusca), Yeniang No.2 (V. quinquangularis), NW196 (V. quinquangularis and V. vinifera), Xiangniang No.1 (V. davidii) and Noble (V. rotundifolia), which was in accordance to the sensory evaluation performed by the judges (Cheng et al, 2018). On the other hand, Wei et al (2018) reported that total phenolic content in V. quinquangularis wines were lower than the wines from Cabernet Sauvignon and Carmenère.…”
Section: Vitis Quinquangularissupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, anthocyanin composition of V. vinifera grapes is widely different than these aforementioned Vitis species, in which non-acylated derivatives represent between 57 to 75 % of total anthocyanins compared to acetyl, coumaroyl and caffeoyl derivatives (Núñez, Monagas, Gomez-Cordovés, & Bartolomé, 2004;González-Neves et al, 2007; Castillo-Muñoz, Fernández-González, Gómez-Alonso, García-Romero, & Hermosín-Gutiérrez, 2009;Gutiérrez-Gamboa et al, 2017). Colorimetric analysis showed that the wines from V. quinquangularis specie presented the most saturated red color compared to other Vitis germplasms cultivated in South of China, such as Moldova (V. vinifera × V. labrusca), Conquistador and Saint-Croix (V. labusca), Yeniang No.2 (V. quinquangularis), NW196 (V. quinquangularis and V. vinifera), Xiangniang No.1 (V. davidii) and Noble (V. rotundifolia), which was in accordance to the sensory evaluation performed by the judges (Cheng et al, 2018). On the other hand, Wei et al (2018) reported that total phenolic content in V. quinquangularis wines were lower than the wines from Cabernet Sauvignon and Carmenère.…”
Section: Vitis Quinquangularissupporting
confidence: 78%
“…Currently, obtain resistance varieties to grapevine diseases without loss of grape berry quality is a crucial challenge for the oenology (Teissedre, 2018). China holds an important abundance of Vitis germplasms resources, which are widely distributed along the country (Cheng et al, 2018). These native species found in China have high vigor, strong grapevine diseases resistance, well climate adaptation, high humidity resistance and low light resistance (Zhang et al, 2012;Liang et al, 2013;Jiao et al, 2014;Liu et al, 2015;Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the Third National Crop Germplasm Resources Survey in China revealed that V. heyneana , V. adenoclada , Vitis davidii , and Vitis pseudoreticulata are widely distributed in the region ( Chen et al., 2020 ). There is a long history of viniculture by using wild grape species in Guangxi, and V. adenoclada grape is an important raw material for wine making in local area ( Cheng et al, 2018 ). Since 2011, research has been carried out to breed the V. adenoclada varieties.…”
Section: Introductionmentioning
confidence: 99%